Final Report for the April 2009 Gulf of Alaska Line-Transect Survey (Goals) in the Navy Training Exercise Area - Rone, Brenda K.; Douglas, Annie B.; Clapham, Phil; Martinez, Anthony; Morse, Laura J.; Zerbini, Alexandre N.; Calambokidis (2009)
Little is known about the occurrence of cetaceans found in offshore waters in the Gulf of Alaska; however, whaling records and a few recent surveys have shown this area to be important habitat. The United States Navy maintains a maritime training area in the central Gulf of Alaska, east of Kodiak Island, and has requested additional information on marine mammal presence and use of this area. To determine the occurrence and distribution of marine mammals in and around the Navy training area, a line-transect visual and acoustic survey was conducted 10-20 April 2009 from the NOAA R/V Oscar Dyson. The primary survey area encompassed nearshore, shelf and offshore pelagic waters of the central Gulf of Alaska. Survey lines were designed to provide equal coverage of the nearshore and offshore habitat. N00244-09-P-0960 Funded by Naval Postgraduate School.